2014
DOI: 10.1146/annurev-clinpsy-032813-153650
|View full text |Cite
|
Sign up to set email alerts
|

Early-Starting Conduct Problems: Intersection of Conduct Problems and Poverty

Abstract: The current paper reviewed extant literature on the intersection between poverty and the development of conduct problems (CP) in early childhood. Associations between exposure to poverty and disruptive behavior were reviewed through the framework of models emphasizing how the stressors associated with poverty indirectly influence child CP by compromising parent psychological resources, investments in children’s welfare, and/or caregiving quality. We expanded upon the most well studied of these models, the fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 128 publications
8
98
0
1
Order By: Relevance
“…Recently, researchers have argued that the family stress model should include direct effects of parental psychological resources on children's emerging disruptive behavior that are not fully accounted for by parenting or other family process stressors (Shaw & Shelleby, 2014), as other researchers have found that effects are not fully mediated by parenting.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have argued that the family stress model should include direct effects of parental psychological resources on children's emerging disruptive behavior that are not fully accounted for by parenting or other family process stressors (Shaw & Shelleby, 2014), as other researchers have found that effects are not fully mediated by parenting.…”
Section: Discussionmentioning
confidence: 99%
“…The age period of 3–5 years old has emerged as a focal point for understanding the emergence of early CU behaviors, because it heralds rapid transitions in children’s physical and cognitive abilities that challenge parents’ abilities to respond to and manage corresponding child behaviors (Shaw & Shelleby, 2014). Moreover, core characteristics related to CU behavior emerge at ages 2–3 years old, including the capacity for empathic concern (Eisenberg & Fabes, 1990), sharing (Fehr, Bernhard, & Rockenbach, 2008), and conscience and rule-compliant behavior (Kochanska, 1997).…”
Section: Callous-unemotional (Cu) Behaviors In Early Childhoodmentioning
confidence: 99%
“…There are two broad threads. Thread one shows the link between poverty and child outcome, and hence, investments take the form of poverty reduction with the concomitant benefits on child outcomes (see, e.g., the link between poverty and child behaviour problems (Shaw & Shelleby, 2014)), on the one hand, and the child outcome benefits of cash transfers which are essentially small regular payments to the most impoverished (Bassani et al, 2013), on the other hand. Thread two shows the extent and range of direct investment in the array of interventions that are known to improve child development outcomes (short and long term), how these are provided for, costed and prioritized.…”
Section: Gaps In Knowledge and Questions For Further Discussionmentioning
confidence: 99%